Perencanaan Konsep Desain Kemasan Produk Soes Kering Menggunakan Metode Kansei Engineering - Sari, Novi Purnama; Alghifari, Muhammad Refah; Rayzidane, Muhammad Rival; Pasha Samudra, Rabbani Dwi (Journal of Industrial Engineering and Technology, 2025)
Dry choux pastry has become one of the popular snack choices at large events, such as festive holidays and other similar occasions. Its crispy texture and melt-in-your-mouth filling can make people fall in love with this snack. Homewever, the commong problem is the packaging, which is not strong enough to keep the pastry crispy.Due to these packaging issues, there is a need for packaging development that can address the complaints consumers have been experiencing. This research aims to develop a packaging design concept for the dry choux pastry product. The method used in this research is Kansei Engineering, a packaging development method based on consumer preferences. PCA (Principal Component Analysis) is used as a supporting method. The observation resulted in 56 samples and 30 kansei words, which were processed into a packaging design concept. The research results obtained a principal component (PC1) with a cumulative proportion value of 94.49%. This component yielded the main packaging design concept, namely portable and uninformative. This concept represents almost all consumer perceptions collected from the research data